Development of a Simple and Quick Method to Assess Base Editing in Human Cells - Xiujuan Lv; Kairui Qiu; Tianxiang Tu; Xiaoxue He; Yuchen Peng; Jinbin Ye; Junhao Fu; Ruzhi Deng; Yuqin Wang; Jinyu Wu; Changbao Liu; Junzhao Zhao; et al. (Elsevier, 2020)
Base editing is a form of genome editing that can directly convert a single base (C or A) to another base (T or G), which is of great potential in biomedical applications. The broad application of base editing is limited by its low activity and specificity, which still needs to be resolved. To address this, a simple and quick method for the determination of its activity/specificity is highly desired. Here, we developed a novel system, which could be harnessed for quick detection of editing activity and specificity of base editors (BEs) in human cells. Specifically, multiple cloning sites (MCS) were inserted into the human genome via lentivirus, and base editing targeting the MCS was performed with BEs. The base editing activities were assessed by specific restriction enzymes. The whole process only includes nucleotide-based targeting the MCS, editing, PCR, and digestion, thus, we named it NOTEPAD. This straightforward approach could be easily accessed by molecular biology laboratories. With this method, we could easily determine the BEs editing efficiency and pattern. The results revealed that BEs triggered more off-target effects in the genome than on plasmids including genomic indels (insertions and deletions). We found that ABEs (adenine base editors) had better fidelity than CBEs (cytosine base editors). Our system could be harnessed as a base editing assessment platform, which would pave the way for the development of next-generation BEs.